The Multimedia Approach in Teaching Physical Fitness as Basis for Physical Education Program - Diosalan, Susan A. (JPAIR Institutional Research, 2016)
Innovations and technological advances in transmitting information play a vital role in the educational system. This experimental research, employing the pretest-posttest design, determined the influence of multimedia in the physical fitness status of students using Zumba video compact disc. A time-series using two groups, the experimental and the control with 30 participants each group from Bachelor in Industrial Education of Capiz State University, Philippines which were selected through random sampling. A descriptive survey was also employed to determine students’ perception towards their exposure to the multimedia Zumba exercise. Data were computed getting the mean scores using the standardized Philippine Physical Fitness Tests. Statistical tools employed to analyze results were descriptive data, frequency, percentage, mean, standard deviation and t-test with 0.05 level of significance. Pre and post results of both groups differ significantly in the muscular strength, flexibility, body composition and cardiovascular endurance. The experimental group perceived that their exposure to the multimedia Zumba exercise developed their knowledge, skills, values and creativity. It is also evident in the result that multimedia teaching approach greatly influenced the effectiveness of the teaching-learning process.